2012
DOI: 10.1038/ismej.2012.148
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation induces syntrophic interactions that impact C, S and N cycling in a sediment microbial community

Abstract: Stimulation of subsurface microorganisms to induce reductive immobilization of metals is a promising approach for bioremediation, yet the overall microbial community response is typically poorly understood. Here we used proteogenomics to test the hypothesis that excess input of acetate activates complex community functioning and syntrophic interactions among autotrophs and heterotrophs. A flow-through sediment column was incubated in a groundwater well of an acetateamended aquifer and recovered during microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 100 publications
(120 reference statements)
0
82
0
Order By: Relevance
“…Groups representing known sulfate reducing bacteria (SRB) previously identified as active at the site (Miletto et al, 2011;Handley et al, 2013)-including members of the Desulfobacteraceae and Desulfobulbaceae-were present in all samples collected during this study, and exhibited dynamic relative abundance fluctuations in many locations. In many instances, relative abundance changes varied over orders of magnitude (Figure 6) despite relatively constant groundwater sulfate concentrations (typically between 8 and 10 mM with slightly elevated concentrations in BND between 8 and 15 mM).…”
Section: Figure 4 | (A)mentioning
confidence: 89%
“…Groups representing known sulfate reducing bacteria (SRB) previously identified as active at the site (Miletto et al, 2011;Handley et al, 2013)-including members of the Desulfobacteraceae and Desulfobulbaceae-were present in all samples collected during this study, and exhibited dynamic relative abundance fluctuations in many locations. In many instances, relative abundance changes varied over orders of magnitude (Figure 6) despite relatively constant groundwater sulfate concentrations (typically between 8 and 10 mM with slightly elevated concentrations in BND between 8 and 15 mM).…”
Section: Figure 4 | (A)mentioning
confidence: 89%
“…Sulfate reduction in the Rifle sediments and groundwater has been previously attributed to Desulfobacter spp. (Milleto et al, 2011;Handley et al, 2012Handley et al, , 2013, while metagenome reconstruction suggested sulfide re-oxidation was attributed to Sulfurovum-and Sulfurimonas-like Epsilonproteobacteria . None of these genomically characterized sulfur-cycling organisms were identified in these samples, indicating the value of sampling different material (planktonic vs sediment-attached) under varying geochemical conditions (iron reduction vs sulfate reduction) to capture the vast physiological diversity in subsurface communities.…”
Section: Metabolic Interdependencies In An Aquifer Microbial Communitmentioning
confidence: 99%
“…To remediate these sites, various fast-degrading substrates (e.g., acetate, ethanol, and lactate) have been used. The substrate injection stimulated microbial populations important to U(VI) reduction, resulting in distinct microbial communities whose functions were dependent upon the choice of substrate (6)(7)(8)(9)(10)(11)(12)(13). However, the use of these fast-degrading, simple substrates has several drawbacks.…”
mentioning
confidence: 99%